A human subcutaneous infection by Microascus ennothomasiorum sp. nov. Issue 2 (13th November 2018) - Brasch, Jochen; Beck‐Jendroschek, Vera; Iturrieta‐González, Isabel; Voss, Karin; Gené, Josepa
Summary: A 60‐year‐old woman presented with a nodular granulomatous skin lesion on her right thumb. It had developed after inoculation of a splinter of wood. Because it was resistant to various therapies, the nodule was finally excised. Complete healing followed this surgery and a melanised filamentous fungus with scopulariopsis‐like morphology was recovered from the dermal tissue. Fitting with no known species, the fungus was subjected to extensive morphological, physiological and genetic investigations. It was characterised by resistance to cycloheximide, growth at 37°C, branched conidiophores with cylindrical annellides in brush‐like groups producing dark conidia in basipetal chains, and cleistothecia with ellipsoidal to slightly reniform ascospores. Genetically it clustered in a well‐supported clade together with Microascus (M.) brunneosporus, Microascus chinensis, Microascus intricatus, Microascus longicollis, Microascus micronesiensis and Microascus onychoides, but formed an independent branch distant from the other Microascus species. Based on its unique genetic characteristics and morphological findings, the isolate is proposed as a new species, Microascus ennothomasiorum . Morphologically it differs from its phylogenetically closest species by its branched conidiophores and ascomata with a peridium of textura intricata . Our observation once again emphasises that dermal granulomas can be caused by uncommon fungi; diagnostics should therefore include appropriate mycological investigations.